HUBUNGAN PENGETAHUAN IBU DENGAN KEJADIAN KARIES GIGI PADA ANAK USIA SEKOLAH 7-9 TAHUN DI SEKOLAH DASAR NEGERI 14 AMBON - CORPUTTY, LINTJE SINTJE; Rehatta, Marlen E (Pasapua Health Journal, 2023)
Introduction: Carious disease in children is common and often occurs but receives less attention from parents with the assumption that the child’s teeth will be replaced by permanent teeth. Factors that cause cavities include tooth structure, oral microorganisms, substrate environment (food), and the length of time food sticks in the mouth.The purpose of this study was to analyze the relationship between mother’s knowledgewith the incidence of dental caries in children aged 7-9 years in elementary schoolsNegeri 14 Ambon. Method: The research method used is an analytic descriptive design using a cross sectional design. The population is all mothers who have children aged 7-9 and children aged 7-9 years at SD 14 Kudamati Ambon, totaling 32 people. Sampling using total sampling technique. The sample in this study amounted to 32 people. Result: The results of the study showed that mothers who had good knowledge about dental caries had children who did not experience dental caries, namely 20 people (95.2%). Evidenced by the results of statistical tests using the chi square test obtained a value of P = 0.000 (α <0.05), which means there is a relationship betweenmother’s knowledge of the incidence of dental caries in Ambon 14 Public Elementary School. Conclusion: The conclusion from the research results was that there was a significant relationship between mother’s knowledge and the incidence of dental caries in school-aged children 7-9 with a value (p = 0.000).